2017
DOI: 10.1002/rcs.1834
|View full text |Cite
|
Sign up to set email alerts
|

Robotic bariatric surgery: A general review of the current status

Abstract: Background: While conventional laparoscopy is the gold standard for almost all bariatric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 56 publications
0
34
0
1
Order By: Relevance
“…In recent years, robotic surgery has been utilized for many intraabdominal operations including bariatric surgery. Robotic surgery offers several theoretical advantages including enhanced three-dimensional imaging, greater dexterity, and precision in tissue manipulation [6]. The robotic approach was initially used for gastric bypass and biliopancreatic diversion [7], but there has been a recent increase in utilization of robotic sleeve gastrectomy (RSG).…”
mentioning
confidence: 99%
“…In recent years, robotic surgery has been utilized for many intraabdominal operations including bariatric surgery. Robotic surgery offers several theoretical advantages including enhanced three-dimensional imaging, greater dexterity, and precision in tissue manipulation [6]. The robotic approach was initially used for gastric bypass and biliopancreatic diversion [7], but there has been a recent increase in utilization of robotic sleeve gastrectomy (RSG).…”
mentioning
confidence: 99%
“…Bariatric procedures are extremely common due to the rapidly increasing incidence of obesity throughout the world. Robotic Roux-en-Y gastric bypass was first reported in 1999 [32]. Early papers showed good outcomes and suggested a learning curve of about 10-15 procedures.…”
Section: Non-pancreatic Robotic Surgerymentioning
confidence: 99%
“…In the laparoscopic bypass procedure, the anastomoses are generally performed with a stapler but many surgeons use a sutured anastomosis with the robot because of enhanced suturing ability made possible by the robot [21]. A meta-analysis of laparoscopic versus robotic bariatric surgery has been reported [32]. The authors identified 14 comparative studies, and found great heterogeneity in operative details.…”
Section: Non-pancreatic Robotic Surgerymentioning
confidence: 99%
“…Laparoscopic procedures in the super morbidly obese can be physically challenging for the surgeon and for the equipment due to limited torque effect of instruments in patients with hepatomegaly, increased intraabdominal fat, and extremely thick abdominal walls. [1][2][3] Robotic surgical systems were introduced in 1997 to overcome the disadvantages of a traditional laparoscopic approach. The application of robotic surgery has increased significantly in the field of general surgery and has become more popular in bariatric procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Horgan and Vanuno described the first Roux-en-Y gastric bypass (RYGB) performing by the robotic system in 2001, and Mohr and team reported the technique of a totally robotic RYGB with a single docking position in 2005. 1,[3][4][5][6][7] In this manuscript, we describe our initial experiences with a robotic approach to bariatric surgery at Siriraj Hospital, Bangkok, Thailand. We present our step-bystep single docking robotic approach to operate sleeve gastrectomy and Roux-en-Y gastric bypass by the da Vinci® Si robotic system (Intuitive Surgical, Sunnyvale, CA, USA).…”
Section: Introductionmentioning
confidence: 99%